RISK OF PRECANCEROUS CERVICAL LESIONS A DESCRIPTIVE STUDY AT SAPURAN HEALTH CENTER, WONOSOBO CITY - Dinta Ayuda Farras; Lintang Dian Saraswati; Praba Ginandjar; Arie Wuryanto (Journal of Public Health for Tropical and Coastal Region, 2020)
Cervical cancer is a disease that attacks women caused by Human Paplilloma Virus. Early sign of this cancer is discovery precancerous cervical lesions. Early prevention of knowing the presence of these lesionss is by early detection of the Visual Inspection Acetic Acid (VIA) method. This study was an observational research using case control design. Samples were taken is 126 people, 63 people as total cases and 63 peoples as control. using simple random sampling. Univariate data analyzed and presented in frequency distribution. Characteristics of respondents in this study include the majority of respondents responden were women above 35 years old (60,3%) and low education or lower than 9 years (78,6%). The results showed that 49,2%% had age of first sexual intercourse <20 years, 10,3% had number of sexual partner >1, and 58,3% respondent had ≥3 number of parity. Woman with number of parity ≥3 had precancerous cervical lesionss.